Patrick Curry, Art and Enchantment: How Wonder Works - Sautter, Cia (Journal for the study of religion, nature and culture, 2024)
Patrick Curry, Art and Enchantment: How Wonder Works (Oxford and New York: Routledge, 2023), 254 pp., $ 35.96 (pbk), ISBN 9781032404677